THE LEXICAL LEVEL OF THE UZBEK LANGUAGE AND THE PLACE OF NEOLOGYS RELATED TO COMPUTER TECHNOLOGIES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article discusses the lexical level of the Uzbek language and the role of words, neologisms in it, and in recent years the lexical level of the Uzbek language is associated with innovative processes, various factors and a certain period. Its richness is evidenced by the neologisms that have come in as a result of the development of computer technology.